Ensuring people's right to participate in the building and perfecting of the legal system in Vietnam today - Van Dai, Nguyen; Hoai Bao, Luu (Universidad Hemisferios, 2025)
Promoting democracy, ensuring people's right to participate in politics, the theory of state governance, and the good state governance are topics of special interest in political science and law in Vietnam as well as in other countries. The driving force and requirement of state governance is to promote democracy and human rights associated with the increased level of people's participation in the organization and operation of the Government in general, and in legislative activities in particular. The article analyzes the theoretical and legal basis of people's right to participate in politics, assesses the current situation, and proposes some solutions to better ensure people's right to participate in politics in law-making in response to the requirements of promoting democracy and ensuring state governance in Vietnam today. At the same time, the right to participate in politics also contributes to strengthening people's trust in the political system, creating momentum for the country's sustainable development. However, for this right to be fully effective, there must be clear legal mechanisms, creating conditions for citizens to participate in politics in a fair and effective manner. When the right to participate in politics is guaranteed, society can become more equitable and progressive, and it can develop more firmly. In that sense, the collection and response to people's opinions and contributions must be carried out according to a clear mechanism, avoiding formalities and ensuring that legal decisions reflect people's will.